Morphological profile and estimation of genetic distance of Simmental crossbred - Agung, Paskah Partogi; Ridwan, M; ., Handrie; ., Indriawati; Saputra, F; ., Supraptono; ., Erinaldi (Indonesian Animal Sciences Society, 2014)
Research was done to study the profile of morphological characteristics of Simmental cross cattle in West Sumatera on several age categories and estimating the genetic distance compared to Simmental pure breed based on morphological parameters. Several morphological parameters of the 82 of Simmental cross cattle in West Sumatera and the 23 of Simmental pure breed has been measured. To analyze morphological data and the genetic distance a discriminant analysis was done. Based on statistical tests (t-test), body length, body height, hip height, hip width, chest circumference, chest width, chest depth, head length, and head height had significant difference (P<0.05) between 24-60 months Simmental pure breed and Simmental cross cattle bulls. Based on the similarity phenotypic analysis, it is known that all subpopulations of cattle in this research had a relatively high value (73.68-78.57%). Chest depth was the highest different morphometric factor (0.910). Morphological distribution map indicated that the Simmental cross cattle (subpopulations Agam and Lima Puluh Kota) evenly distributed across all quadrants (I-IV) while the Simmental pure breed (subpopulations BIB Lembang and BIBD Tuah Sakato) distributed only in the I quadrants and II quadrants. The highest genetic distance was identified between cattle in Agam and BIBD Tuah Sakato while the lowest genetic distance was identified between cattle in Agam and Lima Puluh Kota. Based on phenogram tree structure, the observed Simmental cattle could be classified into 2 clusters, subpopulations of BIBD Tuah Sakato and BIB Lembang that represent Simmental pure breed configured their own cluster as well as a subpopulation of Agam and Lima Puluh Kota that represent Simmental cross cattle configured the others. Key Words: Morphological, Genetic Distance, Simmental Cattle, Cross, West Sumatera